2023
DOI: 10.1021/acsami.2c22990
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Carbazole Dendrons for Solution-Processable Green Emissive Phosphorescent Dendrimers

Abstract: A family of first-generation dendrimers containing 3,5-bis(carbazolyl)phenyl dendrons attached to a green emissive fac-tris(2-phenylpyridyl)iridium(III) core were prepared. The solubility of the dendrimers was imparted by the attachment of tertbutyl surface groups to the carbazole moieties. The dendrimers differed in the number of dendrons attached to each ligand (one or two dendrons) as well as the degree of rotational restriction within the dendrons. The densities of the films containing the doubly dendroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Apart from these typical TADF molecules, researchers have also extended these structures to design of TADF polymers and macromolecules (e.g., dendrimers), , aiming to improve the capability of solution-processing materials, potentially reduce processing cost, and enhance suitability for large-scale applications. Among the examples, Hudson et al . designed a TADF dendimer based on the BPPZ acceptor substituted with dendritic donors, while Yang et al .…”
Section: Thermally Activated Delayed Fluorescence (Tadf)mentioning
confidence: 99%
“…Apart from these typical TADF molecules, researchers have also extended these structures to design of TADF polymers and macromolecules (e.g., dendrimers), , aiming to improve the capability of solution-processing materials, potentially reduce processing cost, and enhance suitability for large-scale applications. Among the examples, Hudson et al . designed a TADF dendimer based on the BPPZ acceptor substituted with dendritic donors, while Yang et al .…”
Section: Thermally Activated Delayed Fluorescence (Tadf)mentioning
confidence: 99%
“…In the latter case, dendronisation of the iridium(III) complex has led to solution-processable materials and OLEDs with good efficiencies in simple architectures. [5][6][7][8][9] Phosphorescent light-emitting dendrimers have generally been designed to have the emissive iridium(III) complex at the core, with the dendrons reducing core-core interactions that can lead to a decrease in the PLQY in the solid state. It has been previously shown that dendron generation, surface groups, and/or the number of dendrons attached to the complex can be used to control solubility and intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their good color purities, high quantum efficiencies, relatively short phosphorescence lifetimes and high thermal stabilities, iridium(III) complexes are being applied as phosphorescent materials for OLEDs. [1][2][3][4][5][6][7][8][9][10][11] For Ir(III)cyclometalate complexes, the metal-to-ligand charge transfer ( 3 MLCT) involved in the emissive triplet excited state and the rigid octahedral structure can effectively facilitate the radiative decay process and suppress the non-radiative decay route. In addition, the color purities of iridium(III) complexes can be tuned via the addition of various substituents.…”
Section: Introductionmentioning
confidence: 99%